Determinant factors of employee retention at EPA management Sdn Bhd Kota Tinggi Johor / Sarasyahida Adam - Adam, Sarasyahida (2012)
The retention of human resources has been shown to be momentous to the development and the accomplishment of the organization’s goals and objectives. This research has been conducted to study the determinants of employee retention at EPA Management Sdn Bhd. The primary aim of this study is to explore the main factors that affect employee retention at EPA Management Sdn Bhd. The data collected through questionnaire from 108 respondents. The survey questions designed to determine three elements of retention which are supervisor support, working environment, and rewards. The result of the study shows that working environment was rated as the most important factors that affect employee retention at EPA Management Sdn Bhd. The results also show that working environment and rewards reveal a strong positive relationship with employee retention meanwhile supervisor support show moderate positive relationship with employee retention.